Bioremediation of Ex-Mining Soil with the Biocompost in the Incubation Experiments - Elvrida Rosa; Sufardi Sufardi; Syafruddin Syafruddin; Muhammad Rusdi (Applied and Environmental Soil Science)
A process called bioremediation can be used to turn abandoned mining sites into useful agricultural land. An alternative to enhancing the quality of the ex-siltstone mining soil so that it can be used again as agricultural land is the application of biocompost fertilizer. This study intends to investigate how biocompost might enhance the ex-siltstone mining soil’s quality in incubation treatments. The composition of biocompost used in this study is ingredient I: (a) cow manure = 50%; (b) chicken manure = 30%; (c) sand = 10%; (d) bacteria (bioactivator) = 10%; ingredient II: ingredient I is mixed with cow manure in a composition ratio of 1 : 2. The ex-mining soils were gathered in the ex-cement mining region of Lhoknga Subdistrict, Aceh Besar District (5.45°N, 95.2°E). Incubation experiments were conducted in incubation pots (approximately 5 kg per pot) that were randomly placed in a greenhouse using a 4 × 4 factorial completely randomized design (CRD) with three replications. The first factor is the ratio of ex-siltstone mining soil : biocompost, which consists of four levels of comparison: control (ex-mining soil not incubated), 1 : 1 (50 : 50), 1 : 2 (33 : 67), and 1 : 3 (25 : 75). The second factor is the incubation period, which has four levels: 0, 2, 4, and 6 weeks with 48 experimental units. Indicators of the impact of biocompost on the physical and chemical quality of ex-siltstone mining soil were examined. The result shows that bioremediation of ex-siltstone mining soil with biocompost application improves the quality of ex-siltstone mining soil by decreasing bulk density and permeability and also increasing porosity, decreasing soil pH from alkaline to neutral, and increasing soil organic C, total N, available P, and total K. The incubation period of ex-siltstone mining soil influences the changes and dynamics of the soil’s chemical properties.